2015
DOI: 10.5114/wiitm.2015.52062
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of the influence of three bariatric procedures on insulin resistance improvement. Should the extent of undiluted bile transit be considered a key postoperative factor altering glucose metabolism?

Abstract: IntroductionInsulin resistance (IR), the essential step in development of type 2 diabetes mellitus (T2DM), resolves quickly after bariatric surgery, but the effectiveness depends on the type of the procedure. Although the long-term influence on IR improvement is well documented, the mechanisms of the ultra-fast response after restrictive and bypass procedures require explanation.AimTo determine IR evolution from the initial preparative period to 6 months after the operation, exposing the rapid postoperative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 68 publications
(71 reference statements)
0
14
0
Order By: Relevance
“…However, the question arises about a plausible underlying mechanism of these associations. One difference between the three bariatric procedures analyzed in this study is the length of bile loop [7]. While the loop created during OLGB is longer than that formed during RYGB, no bile loop is made during LSG.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the question arises about a plausible underlying mechanism of these associations. One difference between the three bariatric procedures analyzed in this study is the length of bile loop [7]. While the loop created during OLGB is longer than that formed during RYGB, no bile loop is made during LSG.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, LSG seems to exert less evident effect on circulating BAs or has no effect at all [20]. In our recent study, we observed the most evident improvement of insulin sensitivity after OLGB [7]. Therefore, we decided to compare the effects of various bariatric procedures (with a long or short bile loop, or without the loop) on the composition and concentration of serum BAs and glucose metabolism in morbidly obese patients.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations